Prefixation In Nias Language - Kristof Martin Efori Telaumbanua; Afore Tahir Harefa (Departement of Mathematics Education, 2023)
Morphology is a branch of linguistics that studies and analyses a word formation. One of the processes of forming a new word is Afixation. Affixation is the precess or result of attaching or adding an affix to a root to form a new word. Affixation can be a prefixation, infixation, suffixation, and confixation. Prefixation is the process of attaching a prefix. Prefix is added that is added to the front of a root or stem. Affix is a grammatical element combined with words and stems that produce derived and inflected forms.This reseacrh is aimed at finding out and describing all prefixes throughly that are found in the Nias Language in detail. It means that this research studies about discussion the process of attaching an affix to the front of the root. The objective of this research is to describes the process of attachih a prefix to the root.